Maternal Occupational Exposure to Polycyclic Aromatic Hydrocarbons and Risk of Oral Cleft-Affected Pregnancies. (May 2013) - Langlois, Peter H.; Hoyt, Adrienne T.; Lupo, Philip J.; Lawson, Christina C.; Waters, Martha A.; Desrosiers, Tania A.; Shaw, Gary M.; Romitti, Paul A.; Lammer, Edward J.
Objective: To evaluate whether there is an association between maternal occupational exposure to polycyclic aromatic hydrocarbons and oral clefts in offspring. This is the first human study of polycyclic aromatic hydrocarbons and clefts of which the authors are aware. Design: Case-control study. Setting, Participants: Data for 1997 to 2002 from the National Birth Defects Prevention Study, a large population-based case-control study in the United States, were analyzed. Maternal telephone interviews yielded information on jobs held in the month before through 3 months after conception. Two industrial hygienists independently assessed occupational exposure to polycyclic aromatic hydrocarbons; all jobs rated as exposed or with rating difficulty were reviewed with a third industrial hygienist to reach consensus on all exposure parameters. Logistic regression estimated crude and adjusted odds ratios with 95% confidence intervals for cleft lip with or without cleft palate and cleft palate alone. Results: There were 2989 controls (3.5% exposed), 805 cases of cleft lip with or without cleft palate (5.8% exposed), and 439 cases of cleft palate alone (4.6% exposed). The odds of maternal occupational exposure to polycyclic aromatic hydrocarbons (any versus none) during pregnancy was increased for cleft lip with or without cleft palate cases as compared with controls (odds ratio, 1.69; 95% confidence interval, 1.18 to 2.40); the odds ratio was 1.47 (95% confidence interval 1.02 to 2.12) when adjusted for maternal education. There was a statistically significant adjusted exposure-response relationship for cleft lip with or without cleft palate ( P trend = .02). Odd ratios for cleft palate alone were not statistically significant. Conclusions: Maternal occupational exposure to polycyclic aromatic hydrocarbons was associated with increased risk of cleft lip with or without cleft palate in offspring.